ASPECTS OF USING TOOLS OF MARKETING STRATEGYOF MANAGEMENT AT MODERN ENTERPRISES - MARTYNIUK, O.; ADASYUK, I. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The current level of development of enterprise management systems is characterized by the separation of the use of methodologies of strategic management and marketing orientation. The relevance of the research topic stems from the objective need to synthesize the concepts of marketing and strategic management for the formation of effective tools that can help the company to ensure the effectiveness of marketing activities. To develop and implement a marketing strategy, the company must be flexible, able to understand and adapt to any conditions, and must learn to influence market mechanisms using various marketing tools. The purpose of the article is an abstract theoretical analysis of marketing strategies for managing the activities of the enterprise, determining the advantages and disadvantages of their implementation based on the application of a systematic approach. The study involved the use of the following methods: analysis, synthesis, scientific abstraction (specifying the categorical-conceptual apparatus of the study); system analysis (theoretical and methodological generalizations, determining the advantages and disadvantages of implementing the tools of marketing management strategy). The results of the research: the theoretical approaches to the definition of the concept of "marketing management strategy" are generalized, the change of priorities of using the tools of strategic management among the world companies is investigated; the subject sphere of use of tools of marketing strategy of management at the modern enterprises is defined; the advantages and disadvantages of implementing the tools of marketing management strategy are formed. The practical value of the obtained results lies in the development of theory and practice of marketing management strategy based on the introduction of modern tools that are key in today’s conditions.